Desenvolvimento, avaliação físico-química e biológica de hidrolisado proteico de resíduos agroindustriais para surubim - Dieterich, Fabiana [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This study evaluates the use of agro-industrial byproducts in aquaculture. To this end, pig liver (PL) and tilapia (Oreochromis niloticus) processing byproduct (TR) were used to produce different hydrolysates for use in animal nutrition. The raw materials PL and TR were hydrolyzed with Alcalase® (A) and Brauzyn® (B) enzyme complexes, resulting in four hydrolysates: PA (PL with A), PB (PL with B), TA (TR with A) and TB (TR with B). The experimental design was completely randomized, 2x2 factorial, where the first factor was the raw materials, PL and TR; and the second, the enzyme complexes, Alcalase® and Brauzyn®, with three replications in industrial scale. The hydrolysis reactor, containing the enzyme/substrate material at 1:200 ratio (w/w), was jacketed for temperature control, and the reaction lasted 60 minutes. After processing, the hydrolysate was analyzed to determine the proximate composition; total and free amino acids and fatty acids profile; and, its use in fish diets. The use of different protein hydrolysates in fish diet was evaluated by the growth performance parameters; metabolic and liver parameters; proximate composition of juvenile pintado real® (Pseudoplatystoma sp). Following a completely randomized design with five treatments and four replications, 200 fish (7.23 ± 0.12 g) were distributed in 20 tanks (500 L) and fed the control diet, without hydrolyzed (CO); two diets added 20% of Alcalase® hydrolysates, PA and TA; and two diets with 20% Brauzin® hydrolysate, PB and TB. During the experimental period the average temperature, pH and dissolved oxygen values were 28.5°C ± 0.4; 7.40 ± 0.26; and 6.21 ± 0.32 U mg L-1, respectively. The Alcalase® hydrolysates had a higher amount of free amino acids compared to the other hydrolysates, regardless of the byproduct used. The tilapia residue hydrolysates had higher mean lipid contents, especially monounsaturated fatty ...

Estudando a utilização de coprodutos agroindustriais para aplicação na aquicultura utilizou-se fígado suíno (FS) e resíduo do processamento da tilápia (RT) (Oreochromis niloticus) na produção de diferentes hidrolisados enzimáticos para aplicação na nutrição animal. As matérias primas FS e RT foram hidrolisadas com complexos enzimáticos Alcalase® (A) e Brauzyn® (B), resultando em quatro hidrolisados: FA (FS com A), FB (FS com B), TA (RT com A) e TB (RT com B). Foi utilizado delineamento experimental fatorial 2x2 inteiramente casualisado, sendo o primeiro fator as matérias-primas, RT e FS, o segundo as enzimas, Alcalase® e Brauzyn® e três repetições em escala industrial. A hidrólise ocorreu em reator encamisado com controle de temperatura, contendo a relação enzima/substrato de 1:200 (p/p), durante 60 minutos. Após o processamento dos hidrolisados foram avaliados sua composição centesimal, perfil de aminoácidos totais e livres e perfil de ácidos graxos e sua aplicação em dietas para peixes. Para avaliar o uso de diferentes hidrolisados proteicos sobre o desempenho zootécnico, parâmetros metabólicos, hepáticos e composição centesimal de juvenis de pintado Real® (Pseudoplatystoma sp), foram distribuídos em delineamento experimental inteiramente casualizado 200 peixes (7,23 ± 0,12 g) em 20 tanques (500 L) com cinco dietas: controle, sem inclusão de hidrolisado (CO); e com inclusão de 20% de hidrolisados: Hidrolisado de fígado suíno com Alcalase® (FA); Hidrolisado de fígado suíno com Brauzin® (FB); Resíduo de tilápia com Alcalase® (TA); Resíduo de tilápia com Brauzin® (TB), totalizando cinco tratamentos e quatro repetições. Durante o período experimental a média de temperatura, pH e oxigênio dissolvido foram equivalentes a 28,5 ± 0,4 ºC, 7,40 ± 0,26 e 6,21 ± 0,32 mg L-1, respectivamente. Produtos hidrolisados com Alcalase® apresentaram ...
Keywords: Peixe - Nutrição; Biotecnologia; Hidrólise; Hidrolisados de proteina; Enzimas; Fishes